The Green Paradigm in Accounting A Critique of Capitalist Dominance in Accounting Practice: Paradigma Hijau dalam Akuntansi : Kritik atas Dominasi Kapitalis dalam Praktik Akuntansi - Rusdi Susanto; Yusuf, Marwah; Daud, Dahniyar (JURNAL ECONOMINA, 2026)
This study aims to critically examine the dominance of capitalism in accounting practices and to propose a green paradigm as an alternative that is more oriented toward social and ecological sustainability. The study employs a qualitative approach grounded in a critical paradigm based on Habermas’s theory of communicative action. Data were collected through in-depth interviews with four informants comprising an academic, an accounting practitioner, an environmental activist, and a corporate manager and supplemented by field notes and the researcher’s reflections. Data analysis was conducted critically to identify patterns of ideological domination in accounting practices, while also revealing power relations, interest biases, and their implications for the marginalization of social and ecological dimensions within modern accounting reporting systems in a more comprehensive and reflective manner. The research findings indicate that accounting is not neutral; rather, it functions as an instrument that reproduces a capitalist orientation through its emphasis on profits and shareholder interests. Accounting practices reduce reality to monetary measures, thereby excluding social and ecological aspects from the reporting system. Furthermore, the claim of accounting’s objectivity is illusory because it recognizes only realities that can be monetized. The findings also indicate that social and environmental reporting tends to function as a tool for symbolic legitimization without driving substantive change. From Habermas’s perspective, this condition reflects the dominance of instrumental rationality, which contributes to the colonization of the lifeworld. Therefore, this study underscores the importance of the green paradigm as an effort to transform accounting toward practices that are more communicative, participatory, and socially and ecologically just.